Desenvolvimento moral: a generosidade sob a ótica de crianças e adolescentes - Vale, Liana Gama do (2006)
In this case study, we investigated, on a psychogenetic context, the judgment of children and adolescents related to generosity and researched the place occupied by this virtue in the moral universe of the participants. Thirty (30) students of a public school from Vitória ES took part in this research, their age group varying between 7 and 13 years old, equally divided as to gender. We performed individual interviews according to the clinical method proposed by Piaget (1926/s.d.; 1932/1994). We used as instruments history-dilemmas that dealt with themes referring to generosity. The obtained results allowed us to verify that, when generosity was counter posed to the satisfaction of one s own interest, the option for the generous action was predominant in all the age groups researched. When counter posing generosity to the obedience of authority, however, the option for obedience prevailed in the age group of the seven years old and diminished on the following age groups. This type of link or the absence of it influenced the judgment of the majority of the participants of all ages as to what concerned the manifestation of generosity towards the other. In all age groups studied, the majority of the interviewed indicated conversation as a consequence of the absence of generosity, but the percentage of this answer is lower on the 7 years old group and increased on the other researched age groups. We could therefore affirm that generosity is a part of the moral universe of children and adolescents, who, although considering its lack in some situations worthy of disapproval, do not indicate punishment as a consequence for this flaw. This case study contributes for the expansion of the research field on morality and offer important subsidies for the proposals of moral education that might contemplate virtues such as generosity.